2013
DOI: 10.1055/s-0033-1339923
|View full text |Cite
|
Sign up to set email alerts
|

Enyne Metathesis Approach towards the Cyclopentane Motif of Jatrophane Diterpenes

Abstract: A short and efficient synthesis of the cyclopentane moiety of the jatrophane diterpene Pl-3 has been developed. The route features an enyne metathesis reaction, and a stereoselective palladium-catalyzed reductive epoxide opening as key steps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Thus, the secondary alcohol was smoothly protected as its TBS ether, and the subsequent reductive opening of the allylic epoxide 31 was carried out following a protocol developed by Rinner et al (Scheme 5). 7 Using their optimized conditions, the desired secondary alcohol 32 was isolated as a single diastereomer in 82% yield. For the remaining two steps toward the first building block, the vinyl group was ozonolyzed to give the β-hydroxy aldehyde 33.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, the secondary alcohol was smoothly protected as its TBS ether, and the subsequent reductive opening of the allylic epoxide 31 was carried out following a protocol developed by Rinner et al (Scheme 5). 7 Using their optimized conditions, the desired secondary alcohol 32 was isolated as a single diastereomer in 82% yield. For the remaining two steps toward the first building block, the vinyl group was ozonolyzed to give the β-hydroxy aldehyde 33.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…After the cleavage of the acetonide in 10 , the obtained diol 20 was treated with the Grubbs second generation catalyst ( Scheme 4 ). 7 Even though TLC control showed that the cyclic compound 21 was the main product of the reaction, all attempts to subject the crude reaction mixture to chromatography, in the presence of air, resulted in a substantial loss of material and 21 was isolated in only 27% yield. It has been conceivable that the ruthenium, forming stable complexes with the hydroxyl groups in close proximity, had been responsible for the degradation of the product.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations